Inequalities and Disparities in Regions connected to Fiscal Decentralization - Gariba, Mohammed Ibrahim (Univerzita Pardubice, 2025)
Fiscal decentralization has emerged as a critical strategy for addressing socioeconomic inequalities and environmental disparities in the contemporary global economy, particularly in developed nations. However, the mechanisms through which fiscal decentralization influences inequalities and disparities remain underexplored. This dissertation investigates the relationship between fiscal decentralization, socioeconomic inequalities, and environmental disparities across unitary, federal, leaders, strong, moderate, and modest OECD countries. Specifically, it addresses three objectives: (1) to examine the moderation role of institutional quality in the relationship between fiscal decentralization and socioeconomic inequalities in unitary and federal OECD states, (2) to assess the mediating role of public digitalization and human capital in influencing income inequalities through fiscal decentralization in OECD states, and (3) to establish the mediating role of regulatory environment in the relationship between fiscal decentralization and environmental disparities in the OECD states. Utilizing panel data between 1990-2022 in a Panel fixed effect, Partial Least Squares Structural Equation Modeling (PLS-SEM), and multigroup analysis, this study reveals that fiscal decentralization significantly reduces socioeconomic inequalities and environmental disparities in specific contexts, with public digitalization and regulatory environments serving as critical mediators in leader and modest groups, while human capital’s mediating role is limited. The findings highlight the context-dependent nature of decentralization’s efficacy and advocate tailored policy approaches that integrate digital infrastructure and regulatory frameworks to foster equitable and sustainable regional development. This dissertation contributes to theoretical frameworks such as fiscal federalism, neoclassical, and new economic geography theories, offering evidence-based insights for policymakers to address the global challenges of inequality and environmental sustainability.
Keywords: fiskální decentralizace; socioekonomická nerovnost; environmentální nerovnosti a regulační prostředí; země OECD; Fiscal Decentralization; Socioeconomic inequality; Environmental Disparity and Regulatory Environment; OECD Countries